B-MAC Design and Analysis for Embedded Sensor Networks - Liu Yumin; Sun Yonghe; XU Fengming; Wang Tao (Institute of Advanced Engineering and Science, 2013)
This paper presents medium access control (MAC) protocol designed for embedded sensor networks. I start with a protocol called MACAW, RTS-CTS-DS-DATA data packet exchange. Then I analyze the properties of some MAC protocols, including S-MAC, B-MAC and IEEE 802.15.4. According to the understanding of S-MAC, some advantages are summarized, such as energy saving, latency reduction, etc. however, there are still some disadvantages, including data packet lost, unfairness, synchronization. And then the similarities and differences between them are discussed. S-MAC is a novel technique to reduce energy consumption, but B-MAC is more efficient with long preamble. Using long preamble, B-MAC achieves collision avoidance and high channel utilization rate. B-MAC can minimize idle listening, but it needs bi-directional communication. Finally, the paper presents B-MAC design process and implementation result on MSP430. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2211